Hemodynamic effects of intermittent pneumatic compression on athletes: A double-blinded randomized crossover study - Maia, F.; Machado, M. V. B.; Silva, G.; Nakamura, F. Y.; Ribeiro, J. (International Journal of Sports Physiology and Performance, 2024)
Purpose There are multiple postexercise recovery technologies available in the market based on the assumption of blood-flow enhancement. Lower-limb intermittent pneumatic compression (IPC) has been widely used, but the available scientific evidence supporting its effectiveness remains scarce, requiring a deeper investigation into its underlying mechanisms. The aim of this study was to assess the hemodynamic effects caused by the use of IPC at rest.